PENGARUH PENERAPAN MODEL PROJECT-BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA MATERI BANGUN DATAR KELAS II SDN WEGOKNATAR - Novenrius Sini Timba, Frederiksen; Apriliani Seda, Benedikta; Bera, Lukas (Jurnal Biogenerasi, 2024)
The purpose of this study is to determine the effect of implementing the Project-Based Learning (PjBL) model on students' learning outcomes in mathematics, specifically in the topic of plane figures, among second-grade students at SDN Wegoknatar. The population of this study consists of 22 second-grade students from SDN Wegoknatar. This research is a quantitative study and employs an experimental design. The research uses a pre-experimental one-group pretest-posttest design. The p-value of 0.001, which is less than 0.005, indicates a significant difference between the pretest and posttest scores, leading to the acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (Ho). The intervention using the Project-Based Learning model has a strong impact on improving mathematics learning outcomes in the topic of plane figures for second-grade students at SDN Wegoknatar. Based on the study results, it can be concluded that the Project-Based Learning model significantly affects students' mathematics learning outcomes in the topic of plane figures. This is evident from the t-test results, which show a significant value of 0.001, smaller than 0.05 (p < 0.05). According to the testing criteria, Ha is accepted, indicating a significant difference in learning outcomes with the use of the Project-Based Learning model. .